Novel bioassay to evaluate biocompatibility of bioactive glass scaffolds for tissue engineering - Boccaccini, Aldo R.; et al. (Advances in Applied Ceramics, 2008)
The aim of the present study was to investigate a novel ex ovo bioassay for the first time using the chick embryo chorioallantoic membrane (CAM) for testing tissue engineering bioceramic scaffolds. Bioglass based scaffolds with porosity in the range of 90-95% were fabricated using the foam replica technique and sintering at 1100°C for 1 h. Scaffolds (5 × 5 × 2 mm3) were placed on the CAM at 10 days of total incubation. The embryos were killed 5 days after implantation. The scaffolds and CAM were explanted, fixed in formalin solution and processed for embedding in methyl methacrylate. Histological analysis using ground sections showed that the scaffolds were surrounded by CAM. There was no occurrence of macrophages or related inflammatory cells. The results described in this paper indicate that the developed bioassay is an appropriate approach as an alternative to conventional animal models to evaluate the biocompatibility of scaffold biomaterials for tissue engineering and regenerative medicine. © 2008 Institute of Materials, Minerals and Mining.
UnivIS-Import:2015-03-09:Pub.2008.tech.IW.LM.novelb
Keywords: Biocompatibility; Bioglass; Chick embryo; Scaffolds; Tissue engineering